DETERMINATION OF CHROMIUM (VI) BY MEANS OF AMPEROMETRIC TITRATION METHOD USING TETRAMETHYLTHIONIN (Proceedings of the YSU B: Chemical and Biological Sciences, 2009)
The interaction of bichromate ions with tetramethylthionin by means of amperometric titration method has been studied. The titration may be carried in the following acidity range: 0.1–5.0 M by sulfuric acid and 0.1–1.0 M by hydrochloric acid. The molar ration between the acting components equals [Cr2O7 2-]:[TMT+ ]=1:2. The obeying to the main law of amperometry continued during the titration of 6.0⋅10-5–1.3⋅10-3 M (0.00624–0.14 mg/mL) bichromate solutions. The technique worked out has been tested analyzing chromium-containing ore with acceptable determination error values (2.44% rel.)
Keywords: bichromate ions; tetramethylthionin; hydrochloric acid; sulfuric acid; titration; chromium-containing ore